Jesus in context : Temple, purity, and restoration - Chilton, Bruce. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1997)
The Proclamation of Jesus seeks to place Jesus in the context of first-century Palestinian Judaism. The authors hope to discern the essence of his preaching, his concept of the kingdom of God, and the place of purity in his teaching and activities. Better methods for assessing not simply the authenticity of reported sayings and deeds, but for tracing the development of tradition are considered. The authors are convinced that most of the Synoptic tradition is authentic, but that much of it has been reinterpreted and recontextualized. Herein lies the real challenge for those investigating the historical Jesus. The Proclamation of Jesus opens up new avenues of study and makes new proposals for understanding Jesus in the context of his place and time.